Structural proteomics : elucidating in vivo structural dynamics of integral membrane proteins by hydroxyl radical footprinting - Zhu, Yi (2012)
We have developed a in vivo hydroxyl radical protein footprinting method for investigating the structure-function relationship of three distinct yet common classes of membrane proteins, a porin protein (OmpF) involved in voltage gating, a heterodimer (integrin αLβ2) important in cell adhesion and signaling, and a receptor-ligand interaction (EGF-EGFR) of a typical receptor tyrosine kinase essential for cell growth and signaling. This work indicates that the hydroxyl radical footprinting technique is a promising approach to study the structural dynamics of the integral membrane proteins directly in the native environment on the cell surfaces, and furthermore, to understand the biological function of this important class of proteins that is challenging to be studied by other structural biological methods.